2020
DOI: 10.51594/ijmer.v1i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality, Customer Satisfaction and Loyalty in Banking Sector of Pakistan

Abstract: The major purpose of the research paper is to measure the quality of service offered by private banks operating in Pakistan. Moreover, it tries to investigate the relationship between service quality, customer satisfaction and loyalty. In order for a bank offer to reach the customers, there is a need for services. These services depend on the type of product and it differs in the various organizations. Service can be defined as an intangible offer by one party to another in exchange of money for Service qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Some authors have shown the influence of company fair practices on growth (Perreti, 2004;Hondeghem & Perry, 2009;Nassè, 2012), and profitability (Nassè, 2019). Other authors such as Tarigan et al (2020) emphasize the link between customer satisfaction and shareholders' value, while Abbasi et al (2019) bring out the relationship between service quality, customer satisfaction and loyalty, Nassè et al (2020) emphasize the relationships between equity and customer satisfaction in relation to product quality through a quantitative analysis. The present research rather shows the effects of internal equity on customer satisfaction in the context of developing countries.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Some authors have shown the influence of company fair practices on growth (Perreti, 2004;Hondeghem & Perry, 2009;Nassè, 2012), and profitability (Nassè, 2019). Other authors such as Tarigan et al (2020) emphasize the link between customer satisfaction and shareholders' value, while Abbasi et al (2019) bring out the relationship between service quality, customer satisfaction and loyalty, Nassè et al (2020) emphasize the relationships between equity and customer satisfaction in relation to product quality through a quantitative analysis. The present research rather shows the effects of internal equity on customer satisfaction in the context of developing countries.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“… Underpinning Theories The Theory of Satisfaction: Vanhamme (2004), Olsen (2002), Abbasi, et al (2019), Nassè (2021 b) portray customer satisfaction as an emotional state. For these authors, equity and emotional reactions are linked to the concept of satisfaction.…”
Section: Literature Review  Conceptsmentioning
confidence: 99%
“…For Gandhi (2011), customer satisfaction is determined by employee's satisfaction. Other authors such as Tarigan et al (2020) emphasize the link between customer satisfaction and shareholders' value, while Abbasi et al (2019) bring out the relationship between on service quality, customer satisfaction and loyalty and Nassè et al (2020) emphasize the relationships between equity and customer…”
Section: Quality and Customer Satisfactionmentioning
confidence: 99%